حدودِ ارتدادوبغاوت : پاکستان،سعودی عرب،مصر اور ملائشیا کے قوانین اور ان کے عملی اطلاقات (Al-Qamar, 2018)
This article studies Sharī̒ah penalties for apostasy and rebellion and their applications in the laws of Pakistan, Saudi Arabia, Egypt and Malaysia. It argues that in Pakistani law, an apostate is given time by the court to repent as many days as he deems fit and this period does not exceed one month. Similarly, according to Saudi Arabian law, an apostate is given a period of at least one month to repent, during which time the apostate will spend time in prison. If he later repents, this is compensated, otherwise it is punishable by death. In Egypt, apostates are given up to 1 month to repent, after which, if they do not repent, they are given death penalty. In Malaysia, apostates are fined. According to the Pakistan Penal Code, a person who commits mutiny is sentenced to life imprisonment and a fine. In Saudi Arabia, mutiny is punishable by death, while in Egypt, mutiny is punishable by up to six months. In Malaysia, anyone who rebels against the ruling regime or participates in any form is punishable by death and sometimes life imprisonment or a fine. According to Islamic law, apostasy and rebellion are punishable only by beheading in Saudi Arabia, while in all three countries, including Pakistan, apostasy and rebellion are punishable by imprisonment, fine or death. However, most of the earlier courts have given relief to the convicts in the punishment and in these three countries the implementation of Shariah punishment is almost non-existent.
Keywords: Sharī̒ah Penalties; Apostasy; Rebellion; laws of Pakistan; Saudi Arabia; Egypt; Malaysia